The serological relationship between Escherichia coli O157 and Yersinia enterocolitica O9 using sera from patients with brucellosis. - Chart, H. (Cambridge University Press, 1992)
Sera from ten patients with positive brucella serology were used to investigate antibody cross-reactions between the O-antigens of Escherichia coli O157 and Yersinia enterocolitica O9. SDS-PAGE profiles of lipopolysaccharide (LPS), purified from strains of E. coli O157 and Y. enterocolitica O9, were reacted with sera by immunoblotting. All ten sera contained antibodies which bound to the LPS of E. coli O157, and five of these sera also contained antibodies which bound to the LPS of Y. enterocolitica O9. Absorption studies using these five cross-reacting sera indicated the existence of at least three epitopes exposed on the O-antigens of E. coli O157 and Y. enterocolitica O9. One antigen binding site appeared to be exposed on the LPS of both organisms, while one epitope was exposed on the LPS of E. coli O157 only, and another on the LPS of Y. enterocolitica O9 only.